2017
DOI: 10.1111/1365-2656.12775
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing lifetime reproductive output: Intermittent breeding as a tactic for females in a long‐lived, multiparous mammal

Abstract: In iteroparous species, intermittent breeding is an important life-history tactic that can greatly affect animal population growth and viability. Despite its importance, few studies have quantified the consequences of breeding pauses on lifetime reproductive output, principally because calculating lifetime reproductive output requires knowledge of each individual's entire reproductive history. This information is extremely difficult to obtain in wild populations. We applied novel statistical approaches that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 80 publications
3
64
0
Order By: Relevance
“…Capital breeding species in fluctuating environments are likely to be particularly prone to skipping breeding episodes when survival takes precedence over reproduction (Stearns, ). Skipped breeding episodes among experienced breeders are known in capital breeding phocid seals, but mechanistic explanations of the process have often relied anecdotally on Boyd’s () finding that body mass accounted for more variation in pregnancy rates in capital breeding than income breeding species (Chambert, Rotella, Higgs, & Garrott, ; Desprez et al, ). Desprez et al () used resighting records at Macquarie Island to investigate intermittent breeding of southern elephant seals Mirounga leonina.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Capital breeding species in fluctuating environments are likely to be particularly prone to skipping breeding episodes when survival takes precedence over reproduction (Stearns, ). Skipped breeding episodes among experienced breeders are known in capital breeding phocid seals, but mechanistic explanations of the process have often relied anecdotally on Boyd’s () finding that body mass accounted for more variation in pregnancy rates in capital breeding than income breeding species (Chambert, Rotella, Higgs, & Garrott, ; Desprez et al, ). Desprez et al () used resighting records at Macquarie Island to investigate intermittent breeding of southern elephant seals Mirounga leonina.…”
Section: Discussionmentioning
confidence: 99%
“…Skipped breeding episodes among experienced breeders are known in capital breeding phocid seals, but mechanistic explanations of the process have often relied anecdotally on Boyd’s () finding that body mass accounted for more variation in pregnancy rates in capital breeding than income breeding species (Chambert, Rotella, Higgs, & Garrott, ; Desprez et al, ). Desprez et al () used resighting records at Macquarie Island to investigate intermittent breeding of southern elephant seals Mirounga leonina. Using a multievent model incorporating uncertain reproductive status and categorizing adult females into breeding heterogeneity classes, they found that there was a survival cost to breeding for females in the infrequently breeding class.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations